2022
DOI: 10.3389/fonc.2021.803986
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Central Neck Dissection for cN1b Papillary Thyroid Carcinoma: A Systematic Review and Meta-Analysis

Abstract: BackgroundThe value of prophylactic central neck dissection (PCND) for papillary thyroid carcinoma (PTC) with clinically evident lateral cervical lymph node metastases (cN1b) remains unclear. Therefore, a systematic review and meta-analysis was conducted to assess the efficacy and safety of PCND.MethodsA comprehensive systematic search was conducted on PubMed, Web of Science, Cochrane library and Embase databases up to September 2021 to identify eligible studies. Controlled clinical trials assessing therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…We show that LND was a risk factor for postoperative hypoparathyroidism. In patients who underwent simultaneous LND with CND, preservation of blood flow during neck dissection may be difficult, consistent with the previous reports 27,28 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We show that LND was a risk factor for postoperative hypoparathyroidism. In patients who underwent simultaneous LND with CND, preservation of blood flow during neck dissection may be difficult, consistent with the previous reports 27,28 …”
Section: Discussionsupporting
confidence: 88%
“…In patients who underwent simultaneous LND with CND, preservation of blood flow during neck dissection may be difficult, consistent with the previous reports. 27,28 In recent years, a variety of new techniques have been reported…”
Section: Discussionmentioning
confidence: 99%
“…Although CND improves disease-specifc survival and reduces local recurrence in cases of LNM [9], prophylactic CND has been reported to not improve long-term outcomes and is related to high hypoparathyroidism rates [10]. Given the increasing awareness about the substantial impact of PTC overdiagnosis, the guidelines of the American Tyroid Association (ATA) recommended and advocated thyroid lobectomy alone and active surveillance as initial treatments for low-risk PTC patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…4 Furthermore, even in cN1b PTC, pCND did not significantly reduce locoregional recurrence (p = 0.09) but was associated with a higher rate of permanent hypoparathyroidism (p = 0.04) and overall complications (p = 0.008). 5 Recent studies have examined the efficacy and safety of pCND in low-risk PTC. Multiple meta-analyses found no significant improvement in disease-free survival (p = 0.38) or overall survival (p = 0.91) with pCND.…”
mentioning
confidence: 99%
“…However, they observed increased risks of complications, including hypoparathyroidism (p < 0.001) and RLN injury (p = 0.002). 6 Furthermore, a large retrospective multicenter study involving 3,214 patients failed to resolve this issue. It showed that pCND did not significantly reduce the risk of locoregional recurrence in cN0 lateral neck (p = 0.498).…”
mentioning
confidence: 99%